Utilizing energy from hydropower plant overflow water - Gorazd Hren; Andrej Predin (Results in Engineering)
Climate change poses significant challenges to the hydropower sector by altering hydrological patterns and increasing the frequency and intensity of extreme weather events. These shifts necessitate improved strategies for infrastructure protection, spillway operation, and mitigation of environmental impacts such as flooding and riverbed erosion. This study proposes an innovative approach that redefines spillwater as a recoverable energy resource through the integration of siphon turbines. These systems are designed to capture and convert excess discharge during high-flow events into additional electrical energy. The concept is evaluated through physical modeling using a scaled siphon turbine in a controlled laboratory flume, complemented by analysis of operational data from an existing hydropower facility. Technical and economic feasibility assessments demonstrate that retrofitting existing infrastructure with siphon turbines can achieve an approximate 5 % increase in energy production. Additionally, the system enhances operational flexibility and resilience under extreme hydrological conditions. The findings highlight a practical and scalable solution for augmenting hydropower generation while improving the adaptability of renewable energy systems in response to climate variability.